Роль органов чувств при ориентации «по хомингу» у постоянноводных амфибий - Бабенко, Л.А.; Пащенко, Ю.И.; Лялюшко, Д.М. (Вестник зоологии, 1973)
Rana esculenta L., R. redibunda P a 11. and Bombina bombina L. were studied for elucidation of their orientation by homing), role of different analysers by means of which the frogs choose the necessary direction of movement and significance of the environment possible factors determining amphibians' movement in the chosen direction. It was established that with elimination of the olfactory organs the orientation in the frogs is disturbed and they move in different directions. Damage of the auditory and sight organs does not result in considerable disturbance of their orientation.